The Relationship Between Compliance and Knowledge of Medical Laboratory Technologists Regarding the Use of Personal Protective Equipment - Rio Saputra Dana; A.A.A. Eka Cahyani; Lia Cahya Sari (Jurnal Kesehatan Cendikia Jenius, 2025)
Medical Laboratory Technologists (MLTs) play an important role in ensuring occupational safety through the use of personal protective equipment (PPE). However, compliance with PPE use in clinical laboratories still faces challenges, even though facilities are available. This study aimed to analyze the relationship between the level of knowledge and compliance of MLTs in using PPE during the pre-analytical phase of clinical laboratories.A quantitative approach with a non-experimental cross-sectional correlational design was employed. The study sample consisted of 33 respondents selected through total sampling, comprising MLTs from three hospitals in Badung Regency, Bali. Data were collected in May–June 2025 using a structured questionnaire that had been tested for validity and reliability (Cronbach’s alpha = 0.933). Data analysis was conducted using descriptive statistics and the Spearman Rank test.The results showed that 96% of respondents had very good knowledge and 96% demonstrated very good compliance with PPE use. The Spearman Rank test revealed a significant positive relationship between knowledge and compliance (p = 0.007; r = 0.458).It can be concluded that higher levels of knowledge among MLTs are associated with greater compliance in PPE use. These findings emphasize the need for continuous education, consistent supervision, and a strong safety culture in clinical laboratories.